Next generation wireless networks - e uthor; Guizani, Mohsen (Wiley, 2006)
Next Generation Wireless Systems and Networks offers an expert view of cutting edge Beyond 3rd Generation (B3G) wireless applications. This self-contained reference combines the basics of wireless communications, such as 3G wireless standards, spread spectrum and CDMA systems, with a more advanced level research-oriented approach to B3G communications, eliminating the need to refer to other material. This book will provide readers with the most up-to-date technological developments in wireless communication systems/networks and introduces the major 3G standards, such as W-CDMA, CDMA2000 and TD-SCDMA. It also includes a focus on cognitive radio technology and 3GPP E-UTRA technology; areas which have not been well covered elsewhere. Covers many hot topics in the area of next generation wireless from the authors$1 (Bown research, including: Bluetooth, all-IP wireless networking, power-efficient and bandwidth-efficient air-link technologies, and multi-user signal processing in B3G wireless Clear, step-by-step progression throughout the book will provide the reader with a thorough grounding in the basic topics before moving on to more advanced material Addresses various important topics on wireless communication systems and networks that have emerged only very recently, such as Super-3G technology, 4G wireless, UWB, OFDMA and MIMO Includes a wealth of explanatory tables and illustrations This essential reference will prove invaluable to senior undergraduate and postgraduate students, academics and researchers. It will also be of interest to telecommunications engineers wishing to further their knowledge in this field.s
Keywords: Mobile & Wireless Communications; Electronic books